2015
DOI: 10.1002/pc.23497
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of poly(aryl ether ketone) based phthalonitrile resins/clay nanocomposites

Abstract: Phthalonitrile‐based composites containing sodium montmorillonite (MMT0) and modified montmorillonites (MMT1 and MMT2) were prepared, respectively. The effect of functionalization, content and ball milling of the clay on the morphology, thermal mechanical, and thermal properties of the composites was thoroughly investigated by such methods as small angle X‐ray scattering, scanning electron microscopy, and dynamic, mechanical, and thermogravimetric analyses. FTIR and dynamic rheology measurements confirmed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 44 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Organic–inorganic hybrid films represent a class of new advanced materials that combine the flexibility and processability of organic polymers with superior mechanical and thermal stability of inorganic phase. Much research was reported on the fabrication of PEEK nanocomposites by using low‐cost conventional techniques such as extrusion and compression molding . To produce composites exhibiting improved properties, different strategies were used to achieve a good dispersion of nanofiller within the polymer matrix, such as ultrasonication, ball milling, wrapping in compatibilizing agents, polymer functionalization, and covalent grafting.…”
Section: Introductionmentioning
confidence: 99%
“…Organic–inorganic hybrid films represent a class of new advanced materials that combine the flexibility and processability of organic polymers with superior mechanical and thermal stability of inorganic phase. Much research was reported on the fabrication of PEEK nanocomposites by using low‐cost conventional techniques such as extrusion and compression molding . To produce composites exhibiting improved properties, different strategies were used to achieve a good dispersion of nanofiller within the polymer matrix, such as ultrasonication, ball milling, wrapping in compatibilizing agents, polymer functionalization, and covalent grafting.…”
Section: Introductionmentioning
confidence: 99%